Application of high pressure-assisted infusion treatment to mango pieces: effect on quality properties - Perdomo Lamilla, Carolina (2020)
The aim of this study was to evaluate the effect of the high pressure-assisted infusion treatment on the quality properties of mango cubes. Factors studied were: sorbitol concentration (20°Brix, 40°Brix, 60°Brix), calcium lactate concentration (0%w/w, 1%w/w, 2% w/w) and pressure level (0.1 MPa, 300 MPa, 600 MPa). Results showed that process factors not only improved the mass transfer during the infusion process but also the solid gain was restricted by the incorporation of the calcium salt. The synergetic effect of pressure level and the addition of calcium salt preserved the mechanical properties. The tonality and chromaticity parameters of mango cubes were preserved by the antagonistic effect of the pressure level and sorbitol concentration. All microbiological counts were below the detection level. The most effective process was 600 MPa-60°Brix-2% w/w since it produced an 81.9% of inactivation of the polyphenol oxidase enzyme, which will allow preserving the final product.